Hotel data privacy: strategies to reduce customers' emotional violations, privacy concerns, and switching intention - Yu, Jongsik; Moon, Hyoungeun; Chua, Bee-Lia; Han, Heesup (Routledge, 2022)
This study develops a solid theoretical framework explaining data vulnerability, psychological anxiety, and switching intention of customers through hotel data privacy. Data privacy developed in this study is classified into four sub-factors. The results of the analysis show that data privacy reduces data breach and access vulnerability, which increases privacy concerns, emotional violation, and switching intention. The results of this study successfully confirm the importance and necessity of data privacy and discover the positive effects of data privacy on hotels, while also providing valuable and meaningful insight based on the positive effects on hotel guests.